Impact of platelet turnover on long‐term adverse cardiovascular outcomes in patients undergoing percutaneous coronary intervention. (19th August 2019) - Tscharre, Maximilian; Farhan, Serdar; Bruno, Veronika; Rohla, Miklos; Egger, Florian; Weiss, Thomas W.; Hübl, Wolfgang; Willheim, Martin; Wojta, Johann; Geppert, Alexander; Huber, Kurt; Freynhofer, Matthias K.
Abstract: Background: Increased platelet turnover and high platelet reactivity are associated with short‐term major adverse cardiovascular events (MACE) after percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS) or stable coronary artery disease (SCAD). We investigated the impact of platelet turnover on long‐term MACE. Methods: Consecutive patients presenting with ACS or SCAD undergoing PCI between 2009 and 2010 were included. All patients received clopidogrel and aspirin as dual antithrombotic therapy regimen. Multivariable Cox proportional hazard models were applied to assess the prognostic impact of platelet turnover (reticulated platelet count [RPC], mean platelet volume [MPV]) and function on long‐term MACE, a composite of cardiovascular death, nonfatal myocardial infarction and nonfatal stroke. Results: In total, 477 patients were eligible. Mean age was 64.3 ± 12.7 years, 68.8% were male. Median follow‐up was 5.8 (IQR 4.2‐6.5) years. Median RPC was 7.6 (IQR 5.6‐10.4) g/L and median MPV was 10.7 (IQR 10.1‐11.3) fL. In univariable analysis, RPC was associated with MACE, both as continuous (HR 1.064 [95%CI 1.021‐1.111]; P = .006) and dichotomized (HR 1.693 [95%CI 1.156‐2.481]; P = .006) variable. After adjustment, continuous RPC (HR 1.055 [95%CI 1.012‐1.099]; P = .010) and dichotomized RPC (HR 1.716 [95%CI 1.152‐2.559]; P = .007) remained significantly associated with MACE. Neither MPV nor platelet function testing was associated with long‐term adverse outcome. Conclusion: Increased platelet turnover is associated with long‐term adverse outcome in patients with coronary artery disease undergoing PCI. Platelet turnover represents a new marker of atherothrombotic risk and might help to guide composition or duration of antiplatelet therapy.